Long-Term Clinical Results of Two-Stage Total Ear Reconstruction of Microtia Using Autologous Cell-Engineered Chondrocytes. Issue 2 (10th November 2022) - Sakahara, Daisuke; Yanaga, Hiroko; Noto, Mariko; Fujimoto, Takuya; Imai, Keisuke
Abstract : Background: Microtia repair requires a large volume of reconstruction material. In pediatric patients, the collectable volume of autologous cartilage is limited, and the impact of surgical invasion and donor-site morbidity can be particularly severe. The authors developed a new treatment method using cultured autologous human auricular chondrocytes that provides a sufficiently large volume of reconstruction material. Methods: Approximately 1 cm 2 of auricular cartilage was collected from the affected site. Chondrocytes were isolated and cultured with autologous serum to accelerate cell proliferation. The cells were subcultured and formed a gel-form mass without a scaffold. In our two-stage implantation, the cultured chondrocytes were first injected into the patient's lower abdomen, where the cells grew into a large, newly generated cartilage in 6 months. Thereafter, this cartilage was sculpted into an ear framework and subcutaneously reimplanted into the new ear location. Clinical outcomes were assessed over a long-term follow-up. Results: Eight patients underwent surgery using cultured autologous auricular chondrocytes from 2002 to 2008. The patients' ages ranged from 6 to 10 years. The follow-up period ranged from 11 to 18 years. None of the patients experienced absorption of cultured chondrocytes after the second stage. Complications included one case of absorption and one case of allergic reaction in the first stage. Conclusions: The authors' patients represent the first successful cases of regenerative surgery for microtia using cultured chondrocytes. No malignant transformation, change in size, deformation, or other abnormalities were observed during the long-term follow-up, demonstrating the safety of cultured cartilage. No major complications occurred. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.